2018
DOI: 10.1590/1678-4162-8940
|View full text |Cite
|
Sign up to set email alerts
|

Produtos de pescado elaborados com resíduos de arrasto: análise físico-química, microbiológica e toxicológica

Abstract: RESUMO Na pesca de arrasto, são inúmeras as espécies de peixe capturadas acidentalmente, compostas, em sua maioria, de espécimes de pequeno tamanho e baixo valor comercial, os quais recebem o nome de rejeito de pesca. O presente trabalho teve como objetivo o desenvolvimento de dois produtos, almôndega e quibe de peixe, tendo como matéria- prima espécies consideradas capturas acidentais na modalidade de pesca de arrasto realizada no litoral do Rio de Janeiro. A identificação taxonômica das espécies teve como re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
6
1
4
Order By: Relevance
“…Regarding protein levels, the levels of the present study were higher than those found by Gonçalves et al (2009) in "piramutaba" (Brachyplatystoma vaillantii) sausage (12.6%). Ribeiro et al (2017), in a study in which kibbe and meatballs were baked from fish pulp obtained from the trawling "mix" category, found lower protein levels (kibbe: 15.10%, meatball: 15.10%) compared to the present study (16.17%). When comparing the lipid results of this same study (kibbe: 4.50%, meatball: 4.40%), the Brazilian flathead sausage was similar (4.41%), although higher than lipid content reported by Silva et al (2012) in a study on the development of croaker sausage (0.57%).…”
Section: Discussioncontrasting
confidence: 87%
“…Regarding protein levels, the levels of the present study were higher than those found by Gonçalves et al (2009) in "piramutaba" (Brachyplatystoma vaillantii) sausage (12.6%). Ribeiro et al (2017), in a study in which kibbe and meatballs were baked from fish pulp obtained from the trawling "mix" category, found lower protein levels (kibbe: 15.10%, meatball: 15.10%) compared to the present study (16.17%). When comparing the lipid results of this same study (kibbe: 4.50%, meatball: 4.40%), the Brazilian flathead sausage was similar (4.41%), although higher than lipid content reported by Silva et al (2012) in a study on the development of croaker sausage (0.57%).…”
Section: Discussioncontrasting
confidence: 87%
“…The technology used to obtain fish MSM is characterized by the passage of the carcass or wastes obtained during the filleting process in a meat-and-bone separation machine (Vidal et al, 2011). The use of such technique arose from the need to take advantage of wastes discards and non-targeted species as raw materials for the acquisition of fish-based products, thus consequently producing products with high nutritional and market value, such as fish-burgers, sausages, crumbed products, dumplings, among others (Durães et al, 2012;Guimarães et al, 2018;Ribeiro et al, 2018). Yet, smoked MSM is a promising product that can serve as basis for the manufacture of other byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, os quibes avaliados (Tabela 3), encontravam-se em desacordo com o citado na literatura (ICMSF, 1986) para psicrotróficos, estando impróprios para consumo, uma vez que apresentaram valores de 7 log UFC.g -1 , aproximadamente. Esses resultados divergem do encontrado por Ribeiro et al (2018), que observaram valores mais baixos, variando de 2 a 3 log UFC.g -1 em quibes elaborados com espécies consideradas resíduo de rede de arrasto.…”
Section: Resultsunclassified